The Effect of Rivastigmine Transdermal Patch on Sleep Apnea in Patients with Probable Alzheimer's Disease - Kim, Hyeyun (Dement Neurocogn Disord, 2016)
BACKGROUND AND PURPOSE: This study was designed to evaluate the effect on sleep of rivastigmine transdermal patch in patients with probable Alzheimer's disease (AD). METHODS: Patients with probable AD underwent a sleep questionnaire, overnight polysomnography and neuropsychological tests before and after rivastigmine transdermal patch treatment. We analyzed the data from enrolled patients with AD. RESULTS: Fourteen patients with probable AD were finally enrolled in this study. The respiratory disturbance index after the rivastigmine patch treatment was improved in patients with probable AD and sleep breathing disorder, compared with that of before treatment (p<0.05). CONCLUSIONS: Rivastigmine transdermal patch application are expected to improve the symptoms of sleep disordered breathing in patients with probable AD. Further placebo controlled studies are needed to confirm these results.